IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM PENINGKATAN STANDAR PENGELOLAAN PENDIDIKAN PADA SMA DI PEKANBARU ERA TRANSFORMASI DIGITAL - Cindy Febby Anjana; Hendri Marhadi; M. Nur Mustafa (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) in improving educational management standards in the era of digital transformation. The study employed a Systematic Literature Review (SLR) approach based on the PRISMA guidelines. Data were collected from scientific articles published between 2020 and 2025. A total of 32 national and international articles were analyzed using thematic synthesis and comparative analysis. The findings indicate that SBM contributes to improving educational management effectiveness through strengthening school autonomy, participatory leadership, stakeholder involvement, collaborative organizational culture, and digital-based management systems. Successful SBM implementation is influenced by leadership commitment, stakeholder collaboration, and schools’ ability to adopt educational technology innovations. The review also shows that digital leadership supports institutional adaptability, decision-making processes, and the development of a responsive educational environment. However, challenges remain, including limited digital competence among educators, organizational resistance to change, and inadequate technological infrastructure. The novelty of this study lies in integrating digital leadership, organizational culture, and digital transformation perspectives within SBM implementation in the digital era.